Amaryllidaceae Alkaloids from Zephyrantes Carinata and Their Evaluation as Cholinesterases (AChE and BChE) Inhibitors - Karina Sierra; Natalie Cortés; Luciana R. Tallini; Warley de S. Borges; Jean Paulo de Andrade; Jaume Bastida; Edison Osorio Durango (Proceedings, 2019)
The subfamily Amaryllidoideae within of the Amaryllidaceae family has an exclusive group of compounds called Amaryllidaceae alkaloids. Galanthamine, the most known Amaryllidaceae alkaloid, is approved by the FDA as an inhibitor of the enzyme acetylcholinesterase (AChE) for the palliative treatment of Alzheimer Disease (AD). However, butyrylcholinesterase (BChE) contributes critically to cholinergic dysfunction associated with AD. Thus, the development of novel therapeutics may involve the inhibition of both cholinesterase enzymes. Zephyranthes carinata, a species of the Amaryllidaceae family, has been reported to have inhibitory activity against cholinesterases. In order to determine the enzymatic inhibition potential, the major alkaloids of bulbs and leaves of Z. carinata were evaluated in both AChE and BChE. A purification and characterization process was made using different chromatographic and spectrometric techniques, and the inhibitory activity was evaluated with the Ellman method. Alkaloidal extracts of bulbs and leaves exhibited an inhibitory activity with IC50 values of 5.8 ± 0.2 and 8.7 ± 0.3 μg/mL, respectively, against AChE. Further, bulb extract showed IC50 values of 77.9 ± 3.4 μg/mL against BChE. Amaryllidaceae alkaloids hamayne, pseudolycorine, galanthine, criasbetaine, tazettine, lycoramine, hippeastidine, galanthamine, trisphaeridine, 3-epimacronine, haemanthamine, lycorine, and vittatine were purified and evaluated for their AChE and BChE inhibitory activities. Lycoramine (galanthamine type) presented the lowest IC50 value in AChE (17 ± 0.7 μg/mL), and trisphaeridine (narciclasine type) showed the lowest IC50 value in BChE (33.1 ± 3.6 μg/mL). Combined major alkaloids (>10%) were analyzed to observe synergistic behavior. The mixture alkaloids lycoramine and galanthine presented IC50 values of 14.55 ± 1.0 μg/mL against AChE, and the lycoramine, trisphaeridine, and vittatine mix presented IC50 values of 38.42 ± 3.4 μg/mL in BChE. These results showed prominent inhibitory activity against AChE and BChE enzymes, indicating their potential as agents for treating AD through a combined strategy.